Upaya Menuju Demokratisasi Pendidikan - Teguh Sihono; Rohaila Yosuf (Jurusan Pendidikan Administrasi FE UNY & ASPAPI PUSAT, 2011)
There are increasing calls for a major change or a paradigm shift in our education system in order for the country to be able to produce a new generation who are dynamic and responsive towards the changing environment. Education is the main instrument to mobilize society toward better future. Therefore the important mechanism in education system such a the regulation, profesionalism, and management should be renewed. The way forward in education should be the democratization of education, the state was make UU No. 22-1999 year, UU No. 32-2004 year (Regional autonomy), UU No. 20-2003 year (Sisdiknas), PP No 19-2005 year (SPN) , Permendiknas No 22, 23, 24-2006 year (KTSP implementation). The implementation of tho curriculum of KTSP the package which give the right and freedom, community participation, organizer authority, supporter institution and stakeholder's should be as planned. There should be serious effort to create educetion democratization in Indonesia. In order for that to happen, the country needcapable human resource who are qualified, superior and competitive.